Pertumbuhan dan Perkembangan Cabai Keriting (Capsicum annuum L.) secara In Vitro pada beberapa Konsentrasi BAP dan IAA - Verdy Soelaiman; Andri Ernawati (Departemen Agronomi dan Hortikultura, 2013)
Curly red pepper (Capsicum annuumL.) is one of the crops that are important and widely cultivated in Indonesia. The purpose of this research was to determine the effect of the use of plant growth regulators BAP and IAA in various doses on the growth and development of curly red peppers in vitro. This research was conducted on March until October 2011 in Tissue Culture Laboratory Department of Agronomy and Horticulture, Faculty of Agriculture, Bogor Agricultural University. This research using Randomized Complete Design with combination of plant growth reguators as the factor. The results showed that combinations of growth regulators significantly influenced root induction, high growth, number of leaves, callus and shoot multiplication. Plant growth regulator combination of 0 mg L-1 BAP + 1 mg L-1 IAA was very good treatment in inducing roots. Combination of 2 mg L-1 BAP + 0.2 mg L-1 IAA effect high growth and shoot induction. Combination of 1 mg L-1 BAP + 0 mgL-1 IAA was the best treatment in increasing number of leaves. While for callus and multiplication, the best treatment was combination of 4 mg L-1 BAP + 0 mg L-1 IAA.Keyword: induction, growth regulators, pepper plant